Predictors of saccadic reaction time among young children in Lusaka, Zambia - Jacqueline M. Lauer; Juha Pyykkö; Anthony Consigli; Mpela Chembe; Tamara Billima-Mulenga; Savanna Henderson; Doug Parkerson; Jukka M. Leppänen; Lindsey M. Locks; Günther Fink; Peter C. Rockers (PLoS ONE, 2026)
Saccadic reaction time (SRT), an assessment of visual processing speed, may afford an accurate and unbiased measure of early childhood development (ECD). Few studies have examined SRT in low- and middle-income countries (LMICs), including its drivers. We sought to identify predictors of SRT as well as to assess the correlation between SRT and concurrent measures of ECD [Global Scales of Early Development (GSED) development-for-age Z-score (DAZ), height-for-age Z-score (HAZ), and head circumference-for-age Z-score (HCZ)], among young children in Lusaka, Zambia. We conducted a sub-study among 299 Lusakan children participating in a 2x2 cluster-randomized trial. SRT was assessed at ~31 months using a screen-based setup with a Tobii Pro Fusion tracker. Associations with household, caregiver, and child characteristics were assessed using univariable regression models; predictors significant at the p < 0.20 level were retained in a multivariable model. Pearson correlation coefficients were calculated to assess associations between SRT and other concurrent measures of ECD. In the multivariable model, characteristics found to be significant predictors of SRT included: being the only child <5 in the household at baseline (β: −10.02, 95% CI: −19.71, −0.33, p = 0.04), length-for-age Z-score (LAZ) at baseline (β: −3.17, 95% CI: −6.31, −0.04, p = 0.047), consuming ≥4 food groups in the past day (β: −10.42, 95% CI: −19.98, −0.86, p = 0.03), and having diarrhea in the past 2 weeks (β: 12.38, 95% CI: 0.71, 24.06, p = 0.04). SRT was significantly negatively correlated with HAZ (−0.176, p < 0.01) and HCZ (−0.132, p < 0.05), but not GSED DAZ. Overall, we identified several significant predictors of SRT among young children in Lusaka, Zambia, including birth spacing, baseline LAZ, dietary diversity, and diarrheal disease. Further research is needed, including in different age groups and geographic locations, to better understand the drivers of slow SRT, and poor ECD generally, in LMICs.